Inclusion in a multicultural nation: Realities through case studies - Balakrishnan, Vishalache (2015)
According to Inclusion Press International, inclusion is not just a ‘disability issue’ but about living full lives, about learning to live together and treasuring diversity and building community. When Malaysia obtained her independence from the Britain in 1957, one of the main ruling was all three ethnicity should live together as one nation. No individual should be excluded from any aspects of education, economy and social. After almost six decades of independence, many individuals in Malaysia are still unhappy with the social injustice due to exclusion based on several factors such as ethnicity and historical roots. In this paper I would like to argue that the minority ethnic group have been side lined due to constitutional rights and current policies. They have to fend for themselves and the social injustice caused many to leave their country of birth to move to other countries where they are treated equally for what they are and not who they are. I suggest that there is a critical need to overlook its political, economic and education policies to ensure a new world which is just and fair.